2016
DOI: 10.3892/mco.2016.977
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oxaliplatin, bevacizumab and oral S-1 for advanced recurrent colorectal cancer

Abstract: Abstract. The aim of this study was to evaluate the efficacy and safety of co-administration of oral S-1 and oxaliplatin (SOX) in combination with bevacizumab (bev) in patients with advanced recurrent colorectal cancer. A retrospective study of 36 patients with advanced recurrent colorectal cancer was performed, of whom 27 received first-line and 9 received second-line SOX+bev chemotherapy between 2010 and 2013 at the Hachioji Digestive Disease Hospital (Hachioji, Japan). The SOX+bev regimen consisted of admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, bevacizumab can be used in combination with conventional antitumor drugs with low side effects (10,11,(22)(23)(24). A number of clinical trials with patients with recurrent and metastatic HNSCC and OSCC revealed that bevacizumab in combination with other molecular-targeted therapies, chemotherapies and/or radiation therapy led to improved OS and progression-free survival in numerous types of cancer, including HNSCC (10,11,(22)(23)(24)29). Previous studies reported that bevacizumab in combination with S-1 yielded modest to high efficacy against a number of types of cancer, such as advanced recurrent or metastatic colorectal cancer, advanced gastric cancer, advanced lung cancer, advanced esophageal carcinoma with mild and acceptable toxicities, especially as a second-or third-line therapy (12,23,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bevacizumab can be used in combination with conventional antitumor drugs with low side effects (10,11,(22)(23)(24). A number of clinical trials with patients with recurrent and metastatic HNSCC and OSCC revealed that bevacizumab in combination with other molecular-targeted therapies, chemotherapies and/or radiation therapy led to improved OS and progression-free survival in numerous types of cancer, including HNSCC (10,11,(22)(23)(24)29). Previous studies reported that bevacizumab in combination with S-1 yielded modest to high efficacy against a number of types of cancer, such as advanced recurrent or metastatic colorectal cancer, advanced gastric cancer, advanced lung cancer, advanced esophageal carcinoma with mild and acceptable toxicities, especially as a second-or third-line therapy (12,23,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%